Antara Pluralisme Liberal danToleransi Islam - Ryandi Ryandi (Universitas Darussalam Gontor, 2013)
Religious plurality is a natural phenomenon that occurs in the reality of life. In the midst of the diversity of ideological differences and truth claim, indeed every believer is required to tolerate all sorts of concepts conceived by the ideology and truth claim. It is obvioulys become a logical implication because each ideology and truth will lead followers too surely believe all the religion dogma; including claim of salvation. However, in view of liberalism, tolerance alone is not enough. Religious Pluralism needs to be propagated as a solution to religious harmony. In the other words, Religious Tolerance in the view of Liberal is Religious Pluralism. Religious Pluralism, as part of Western postmodern discourses attempt to relativize truth claims of religions, so there is no truth can be acknowledged. Islam was included. This concept indeed is in contradiction to the concept of tolerance in slam that acknowledges religious plurality in society without coercing to believe religions truth claim. Islam is conceptually recognized Plurality, but firmly reject Pluralism.